2017
DOI: 10.1051/sicotj/2017056
|View full text |Cite
|
Sign up to set email alerts
|

Major destructive asymptomatic lumbar Charcot lesion treated with three column resection and short segment reconstruction. Case report, treatment strategy and review of literature

Abstract: Charcot's spine is a long-term complication of spinal cord injury. The lesion is often localized at the caudal end of long fusion constructs and distal to the level of paraplegia. However, cases are rare and the literature relevant to the management of Charcot's arthropathy is limited. This paper reviews the clinical features, diagnosis, and surgical management of post-traumatic spinal neuroarthropathy in the current literature. We present a rare case of adjacent level Charcot's lesion of the lumbar spine in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…These challenges make the development of additional salvage techniques useful. Several authors have separately reported 3-column spinal shortening when a large defect is present, [7][8][9] as was used in our Case 2. However, the technique of thecal transection and placement of structural graft in the canal represents an additional tool.…”
Section: Discussionmentioning
confidence: 96%
“…These challenges make the development of additional salvage techniques useful. Several authors have separately reported 3-column spinal shortening when a large defect is present, [7][8][9] as was used in our Case 2. However, the technique of thecal transection and placement of structural graft in the canal represents an additional tool.…”
Section: Discussionmentioning
confidence: 96%
“…Numerous techniques are used for anterior column reconstruction following vertebral resection [12]. Conventionally, a strut autograft is used, either a resected rib, tricortical iliac, fibular strut, or allograft [13,14]. No adequate stability is provided when using ribs.…”
Section: Discussionmentioning
confidence: 99%
“…No adequate stability is provided when using ribs. Being fragile, with high plastic deformation and a small contact area [14]. As for tricortical iliac struts, fashioning the shape and size is difficult, having relatively small weight-bearing surfaces also increased donor site morbidity [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Additional stability may be achieved through the addition of extra rods (eg, four-rod or more rod constructs) and increasing the diameter of the rod 28,29 using stiffer materials (eg, cobalt chrome plus over titanium products). 28 Multiple previous publications 19,21,22 detail these surgical techniques in various presentations of Charcot spine arthropathy. Although fixed angle screws add stability, it may increase the difficulty of passing the rod across the site of Charcot.…”
Section: Surgical Treatment Considerations For Charcot Spinal Arthrop...mentioning
confidence: 99%